Fertilização nitrogenada de hortaliças cultivada em plantio direto em sucessão a plantas de cobertura - Branco, Roberto B. F.; Blat, Sally F.; Gimenes, Tais G. S.; Nowaki, Rodrigo H. D. [UNESP]; Araújo, Humberto S.; Salles, Fernando A. (FapUNIFESP (SciELO), 2017)
The production of horticultural crops in no-tillage and in rotation with cover crops reduces the dependency in nitrogen fertilizer, due to increased soil organic matter and by biological fixation performed by legumes. Thus, the aim of this work was to study rates of nitrogen fertilization and cover crops in the agronomic performance of tomato and broccoli grown under no-tillage. The experiment was conducted in a split plot design with four replications. Treatments consisted of cover crops, sunn hemp and millet, and four rates of nitrogen fertilization (0, 50, 100 and 200 kg/ha of nitrogen), for both the tomato and broccoli crops. All soil management was performed in no-tillage. For tomato crops we evaluated the plant growth, the nitrate concentration of sprouts and fruits and yield of commercial and non commercial fruits. For broccoli we evaluated plant growth and yield. There was an interaction effect between cover crop and nitrogen rates to tomato growth measured at 100 days after transplanting, for plant height, number of fruit bunches, dry mass of leaves and diameter of the stalk. The tomato commercial fruit number and yield showed maximum values with 137 and 134 kg/ha of N respectively, on the sunn hemp straw. The nitrate concentration of the tomato sprouts was linearly increasing with the increase of nitrogen rates, when grown on the millet straw. For broccoli production, the maximum fresh mass of commercial inflorescence was with 96 kg/ha of N, when grown on the millet straw.
Nitrogen fertilization of vegetables cultivated under no-tillage after cover crops
Keywords: Brassica oleraceae var. itálica; Crotalaria junceae; Pennisetum americanum; Soil management; Solanum lycopersicon